River mechanics - Yalin, M. Selim (Mehmet Selim), 1925- (Pergamon Press, 1992)
Understanding the mechanism and behaviour of rivers flowing in alluvium is a most challenging subject. The conditions presented by a natural river are far from simple: the flow varies with location and time, and the granular structure and cohesive properties of the alluvium are rarely homogeneous. River Mechanics addresses this subject and aims to improve the understanding and formulation of the fluvial processes which occur in rivers. Topics covered include the interpretation of turbulence in the light of recent advances in the field, and current thinking on the regime concept.